The impact of local labour markets on investment in further education: Evidence from the England and Wales youth cohort studies. - Rice, P (Springer, 1999)
The paper focuses on the individual's choice of activity on completion of compulsory schooling – to remain in full-time education or to seek employment – and the factors influencing this decision. Information from the England and Wales Youth Cohort Studies, coupled with labour market data, is used to estimate of logit model of choice and assess the role played by social and market factors. The results show that labour market conditions play an influential role in determining outcomes, particularly in the case of young males with weaker academic qualifications. Consistent with the time-series evidence, we find that participation rates in further education for both males and females are positively related to the unemployment rate in the local labour market, the effects being greater at times of economic recession when unemployment rates are rising.